Pelatihan Penggunaan Microsoft Office Dalam Rangka Mendukung Pembuatan Proposal Tugas Akhir Kepada Para Siswa/I SMK Wisata Harapan Massa Depok - Akrom (CV. Multi Kreasi Media, 2022)
Education is an important activity in soecity, that will changes society, in Formal Education Students will give a final project which is one of the graduation requirements, writing a final project, is still considered heavy for students and school students especially SMK Wisata Harapan Masa Depok, to do this writing, students will use commonly used software, namely Microsoft Office Word, Microsoft Office Word is one of the most famous software or software in the world, to use Microsoft Office Word which it's true that students need to master the techniques, therefore to help the rest and our students from the PKM Lecturer team at Pamulang University will conduct training and training with the title